2008
DOI: 10.1021/jf801670p
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alkalization on the Antioxidant and Flavanol Content of Commercial Cocoa Powders

Abstract: Cocoa is a food ingredient that is important for the contribution of flavor to foods but is also associated with potential health benefits. The chemistry thought to be responsible for its cardiovascular health benefits is the flavanol (flavan-3-ol) antioxidants. Evidence from the literature indicates that natural cocoas are high in flavanols, but when the cocoa is processed with alkali, also known as Dutch processing or Dutching, the flavanols are substantially reduced. This paper provides a survey of the phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
110
3
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(130 citation statements)
references
References 24 publications
14
110
3
3
Order By: Relevance
“…A total of 30 g fine particles of bagasse was poured in 500 mL KOH solution (10 %) and stirred for one night. Addition of KOH solution to bagasse particles facilitated the elimination of colorants, organic acids, lipids and proteins in the cellulosic structure of bagasse, and mostly important alkalized the surface of particles (27,28). The alkalized particles were then washed with sufficient water until pH 7 in the eluate solution was achieved.…”
Section: Preparation Of Dithizone-modified Bagasse Adsorbentmentioning
confidence: 99%
“…A total of 30 g fine particles of bagasse was poured in 500 mL KOH solution (10 %) and stirred for one night. Addition of KOH solution to bagasse particles facilitated the elimination of colorants, organic acids, lipids and proteins in the cellulosic structure of bagasse, and mostly important alkalized the surface of particles (27,28). The alkalized particles were then washed with sufficient water until pH 7 in the eluate solution was achieved.…”
Section: Preparation Of Dithizone-modified Bagasse Adsorbentmentioning
confidence: 99%
“…Miller et al demonstrated a steady decrease in flavanol content with increasing pH in cocoa powder 43 . As a result, Dutched chocolate typically exhibits low total flavanol content 11,43 . A recent study demonstrated that Dutching decreases C and EC levels in cocoa powder by 38% and 67% respectively 6 .…”
mentioning
confidence: 98%
“…doi: 10.17221/265/2016-CJFS Cocoa powder and baking chocolates are the cocoa products with the highest amount of non-fat cocoa solids, followed by dark chocolate which contains around 20-29.5% non-fat solids and is derived from cocoa liquor (Miller et al 2008). In recent years, several studies have documented the beneficial effects of dark chocolate on human health.…”
mentioning
confidence: 99%